2009
DOI: 10.1038/onc.2009.126
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 inhibits breast cancer growth and pulmonary breast cancer metastasis

Abstract: The loss of expression of the transcription factor GATA3 in breast tumors has been linked to aggressive tumor development and poor patient survival. In the present work, we address potential roles for GATA3 in breast tumor lung metastasis and progression. Using an aggressive breast cancer cell line, which metastasizes specifically to the lung, we show that GATA3 expression results in reduced tumor outgrowth in the mammary fat pad and lower lung metastatic burden in nude mice. Specifically, GATA3 expression inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
114
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 36 publications
10
114
0
2
Order By: Relevance
“…Indeed, FOXA1 has been shown to be transcriptionally regulated by GATA3 (Kouros-Mehr et al, 2006). The importance of GATA3 expression in repressing tumorigenesis is highlighted in a previous study, which showed that exogenous GATA3 expression inhibited the growth and pulmonary metastatic activity (both phenotypes associated with FOXC-expressing BLBCs) of a highly aggressive breast cancer cell line (Dydensborg et al, 2009). The requirement of GATA3 for the ability of BRCA1 to repress basal-like genes, would therefore, explain why BRCA1 mutant breast tumors show elevated expression of basal-like markers such as FOXC1 and FOXC2.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, FOXA1 has been shown to be transcriptionally regulated by GATA3 (Kouros-Mehr et al, 2006). The importance of GATA3 expression in repressing tumorigenesis is highlighted in a previous study, which showed that exogenous GATA3 expression inhibited the growth and pulmonary metastatic activity (both phenotypes associated with FOXC-expressing BLBCs) of a highly aggressive breast cancer cell line (Dydensborg et al, 2009). The requirement of GATA3 for the ability of BRCA1 to repress basal-like genes, would therefore, explain why BRCA1 mutant breast tumors show elevated expression of basal-like markers such as FOXC1 and FOXC2.…”
Section: Discussionmentioning
confidence: 97%
“…11,20,21 There is a considerable amount of evidence indicating that GATA3 inhibits breast carcinogenesis and cancer progression. [5][6][7] In contrast, little is known about the role of GATA3 in bladder cancer outgrowth. In the present study, we demonstrate that loss of GATA3 promotes bladder cancer cell migration and invasion, but not cell proliferation, by regulating key molecules involved in tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…7 It was likely that reversing EMT was also a mechanism responsible for suppression of breast cancer invasion and metastasis by GATA3. Overexpression of GATA3 in a GATA3-deficient breast cancer line resulted in upregulation of an epithelial marker (i.e., E-cadherin) and downregulation of mesenchymal markers (i.e., vimentin, N-cadherin) as well as MMP-9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that GATA-3 expression is associated with good prognosis through its ability to promote differentiation in breast cancers may not fully explain how GATA-3 functions to suppress the metastatic properties of breast cancers. It has recently been demonstrated that GATA-3 overexpression in MDA-MB-231 breast cancer cells, which are a basal human breast cancer cell population, could impair mammary tumor growth and lung metastasis without promoting the differentiation of these cells (Dydensborg et al, 2009). Whether GATA-3 directly modulate the expression of genes involved in breast cancer metastasis, independently of its effects on breast cancer differentiation, will require further investigation.…”
Section: Gata-3 Is a Marker Of The Luminal Subtype In Breast Cancermentioning
confidence: 99%